2023
DOI: 10.3390/microorganisms11030756
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and Tick-Borne Pathogens in Recreational Greenspaces in North Central Florida, USA

Abstract: Tick-borne infections are an increasing medical and veterinary concern in the southeastern United States, but there is limited understanding of how recreational greenspaces influence the hazard of pathogen transmission. This study aimed to estimate the potential human and companion animal encounter risk with different questing tick species, and the bacterial or protozoal agents they carry in recreational greenspaces. We collected ticks bimonthly along trails and designated recreational areas in 17 publicly acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
(116 reference statements)
1
1
0
Order By: Relevance
“…The pathogen was not detected in either D. variabilis or A. maculatum ticks, which were also collected in the study [ 313 ]. The findings from Bhosale et al [ 312 ] and Noden et al [ 313 ] support the previous supposition that A. americanum ticks are the vector of B. coco .…”
Section: Prevalence Of Babesia Cocosupporting
confidence: 72%
See 1 more Smart Citation
“…The pathogen was not detected in either D. variabilis or A. maculatum ticks, which were also collected in the study [ 313 ]. The findings from Bhosale et al [ 312 ] and Noden et al [ 313 ] support the previous supposition that A. americanum ticks are the vector of B. coco .…”
Section: Prevalence Of Babesia Cocosupporting
confidence: 72%
“…A study of ticks and tick-borne pathogens in recreational greenspaces in Gainesville (Florida) conducted by Bhosale et al [ 312 ] in 2021 collected questing ticks of six species belonging to various genera, including Amblyomma ( A. americanum , Amblyomma maculatum Koch, 1844), Dermacentor ( Dermacentor variabilis Say, 1821), Haemaphysalis ( Haemaphysalis leporispalustris Packard, 1869), and Ixodes ( Ixodes affinis Neumann, 1899, Ixodes scapularis Say, 1821); however, B. coco DNA was detected only in A. americanum . The infection rate was very low, only 7 out of 1076 lone star ticks were infected with the pathogen [ 312 ]. Similarly, Noden et al [ 313 ] found that only 22 out of 4714 questing lone star ticks collected in 2017 and 2018 in Oklahoma City were infected with B. coco .…”
Section: Prevalence Of Babesia Cocomentioning
confidence: 99%